Cooperative Extension Builds Community Capacity Through Inclusive Engagement - Martha C. Monroe; Alicia Betancourt; Sandra K. Thompson; Dreamal Worthen (The University of Alabama, 2022)
The Cooperative Extension System, a component of every land-grant university, is well positioned to take a leadership role in community engagement in every state. In Florida, a new program called Community Voices, Informed Choices (CIVIC) builds capacity among county and state faculty from the state's two land-grant universities to engage community members in the process of resolving contentious issues through democratic governance. CIVIC strengthens partnerships with historically underserved communities, offers programs and activities to promote deliberative discussion, and facilitates interest in moving toward solutions. Case studies from three communities illustrate the CIVIC process and demonstrate how Extension faculty help communities help themselves.